Proposal for Including English-speaking Quebecers in the Programme d'accès a l'égalité en emploi (PAÉE) - Bourhis, Richard Y. (QUESCREN Lunch & Learn Series, 2024)

Swimming Upstream : Investigating the Barriers to Aquatic Equity for Québec’s English-speaking BIPOC Youth Communities - Porras-Gil, Javier Armando (2023)

They “Could Care for Our Elderly in Our Homes” : The Historical Impact of Black Caregivers - Williams, Dorothy W. (Working Paper, 2023)
My aim is to interrogate prevalent assumptions about health and social services through a survey of notable chapters in the history of Black caregiving in Quebec. The assumptions have created expectations and a false narrative built upon historical myths and erasures that undergird the provincial population’s understanding of its relationship with Black caregivers. Blacks, both Francophone and Anglophone, though not exclusively so, have had significant connection to the care and well-being of Quebec’s residents. Black caregiving in Quebec is not recent—indeed, Black caregivers have been intimately tied to Quebec’s labour force aspirations and development for centuries. Even so, it is rarely acknowledged, to the point of being virtually unknown. This paper seeks to address those gaps in the narrative by presenting a timeline dating back to the 17th century. It will reveal intricate connections between the different periods when it comes to segregation, prejudice, migration, immigration quotas, and bans.

The QFHSA Welcomes the Appointment of a Federal Special Representative on Combatting Islamophobia - Quebec Federation of Home and School Associations (QFHSA) (2023)

QCGN Statement on Murder of Muslim Family in London, Ontario : Human Rights and Freedoms Are Not to be Taken for Granted - Quebec Community Groups Network (QCGN) (2021)

Prioritizing Student Diversity in Québec’s Education System - Advisory Board on English Education (2021)
In previous briefs to the Minister, the Advisory Board on English Education (ABEE) has given advice on inclusion in the classroom and on Indigenous education, so this brief will not address these two issues directly. It will, instead, consider the impact of discrimination and the promotion of inclusion in the school environment, the curriculum, student achievement, and teacher education. Much of the research we have identified relates to racism, and there are certainly issues specific to racist behaviour, but we recognize that the mindset that causes racist behaviour often causes discrimination against “others” of all sorts and that the remediating strategies are often similar.

Executive Summary & Final Report - Task Force on Equity, Diversity, and Inclusion of the Lester B. Pearson School Board (2021)
The purpose of this document is to present the results of deliberations and evidence-based recommendations of the Task Force of Lester B. Pearson School Board (LBPSB) on Diversity, Equity and Inclusion.

Call for Papers : The Impact of Black Lives Matter Movement in the Era of COVID-19 Pandemic - International Journal of Community Development & Management Studies (IJCDMS) (2020)

Black in Quebec : Systemic Racism in Our History - Davids, John; Fang, Xiaoyan; Galutira, Aileen (2020)

Redefining the Black Experience in Montreal: One Institution at a Time - The Project Woke Interns (Black Community Resource Centre (BCRC), 2020)
Project Woke interns identified and investigated three critical themes affecting the Black community in Montreal. An analysis of societal issues and Canada’s Anti-Racism Strategy Project revealed harmful anti-human rights gaps affecting the Black Community. The findings from several consultations further validated these gaps. A comprehensive list of recommendations is included along with next steps as a continuation to advance Black human rights in Montreal, and elsewhere, along with the support of government and non-government actors.

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2020)

Response to CAM Report on Systemic Racism in the Arts - English Language Arts Network (ELAN) (2019)

Black-White Differences in Canadian Educational Attainments and Earnings - Masella, Rosalie; McIntosh, James (Collaborative Unity and Existential Responsibility, 2019)
Data from two large Canadian surveys are used to analyze educational and earnings performance of Blacks and Whites. The main purpose of this study is to determine how well blacks perform relative to Whites in these two areas.

Bill 21 Discriminates Against Quebecers : Statement from ELAN - English Language Arts Network (ELAN) (2019)
Keywords: Official Language Minority Community (OLMC)

ELAN Inclusion Plan - English Language Arts Network (ELAN) (2019)
In summer 2017, after several years of internal discussion, the English Language Arts Network (ELAN) embarked on a process of creating an inclusion plan. This plan addresses our overall direction as an organization, as well as our work in the specific areas of membership, human resources, governance, advocacy, and communications. At the heart of this plan is an acknowledgement that our work on inclusion and diversity is ongoing, will evolve, and will involve mistakes. It is active work, involving all of us and all parts of ELAN. When ELAN began in 2004, the organization was focused on building positive bridges between the French- and English-speaking arts communities. This focus will remain present throughout our work. However, we recognize that in the fifteen years since ELAN started, the context of the arts community has shifted and other issues have been raised.

Semaji - Black Community Resource Centre (BCRC) (2017)

Semaji - Black Community Resource Centre (BCRC) (2017)

Semaji - Black Community Resource Centre (BCRC) (2017)

Semaji - Black Community Resource Centre (BCRC) (2016)

ACDPN Proposes Roadmap for Access to Prevention Services for Black English-speaking Families - African Canadian Development and Prevention Network (2013)

QCGN Marks End of Notre Home Tour with Benefit Concert for Kids Help Phone - Quebec Community Groups Network (QCGN) (2013)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2012)

Briefs Submitted to the Minister of Education, Recreation and Sports : 2012 - Advisory Board on English Education (2012)

Brief Addressed to the Committee on Culture and Education and Bill 56 : An Act to Prevent and Deal with Bullying and Violence in Schools - Quebec Federation of Home and School Associations (QFHSA) (2012)
The Quebec Federation of Home and School Associations (QFHSA) welcomes the opportunity to comment on Bill 56, An Act to prevent and deal with bullying and violence in schools.

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2012)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2011)

The Positive Ticket Pilot Program : A Feasibility Study - Low, Katherine (Black Community Resource Centre (BCRC), 2009)
The Positive Ticket Project was started in Richmond BC, and aims to improve the relationship between youth and police by way of positive interaction. Officers give out the positive tickets to neighbourhood youth displaying positive behaviour, which can be as simple as engaging in safe play or helping a community member. The positive tickets, which are business card size with positive messages printed on them, are combined with gift vouchers donated by and redeemable at local businesses. The real value of the project lies in the positive communication and interaction it creates between the officer and the youth. The Black Community Resource Center in Côte-des-Neiges wishes to implement a Positive Ticket Pilot Project in their neighbourhood in the summer of 2010.

Black Communities Speak Out About Violence - Tichit, Laurence; Jaccoud, Mylène (Black Community Resource Centre (BCRC), 2009)
This project was an initiative of six Black community organizations in Montreal concerned with the problem of violence. It was designed to unfold in three consecutive phases: 1) establish a subject overview by conducting focus groups with members of Montreal's Black communities, 2) organize a roundtable discussion with key people involved in the issue, and 3) develop an intervention plan. This report examines each of these phases which were aimed at defining the bases for mobilization and presenting possible strategies to address the issue of violence within the Black communities.

BCRC Newsletter - Black Community Resource Centre (BCRC) (2008)

BCRC Newsletter - Black Community Resource Centre (BCRC) (2004)

Open and Public Inquiry into the Death of Mr. Rohan Wilson - Alliance Quebec (AQ) (2004)

"Hate is Hate" - Alliance Quebec (AQ) (2003)

Questions of Race are Inevitably Tied to Questions of Language - Alliance Quebec (AQ) (2003)

Quebec Should End Discrimination in Education - Alliance Quebec (AQ) (2002)

Alliance Quebec Calls on Quebec Government to End State-Sponsored Harassment of Ethnics - Alliance Quebec (AQ) (2002)

Villeneuve's Comments Constitute Hate Propoganda : AQ - Alliance Quebec (AQ) (1996)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1996)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1995)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1991)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1986)

National Regional Committee National Congress of Black Women Report - Montreal Regional Committee National Congress of Black Women (1981)
The objectives of this Conference were aimed at sensitizing the general public (Black and White) i.e. parents and children, students and teachers, governmental and para-public organizations, to the racism and sexism found in the textbooks used in our school system, to develop solutions to these problems and to use our collective strength to bring about constructive social change.

Final Report on the Aspirations and Expectations of the Quebec Black Community with Regard to Education - The Black Community Work Group on Education (1978)